Pengaruh Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Dan Gross Profit Margin (GPM) Terhadap Pertumbuhan Laba - Apriani Sumantri Sindi Njiung; Paskalis Seran; Lambertus Sie; Maria Bernadethe Mawarni Gelu Wutun (AKSIOMA : Jurnal Manajemen, 2025)
The population in this research is PT Exploitasi Energi Indonesia Tbk, the sample in this research is the quarterly financial report data of PT Exploitasi Energi Indonesia Tbk for the period 2016-2023. The data collection technique used is a documentation data collection technique that is accessed via the web and sites related to company history and company financial reports. Data analysis uses descriptive statistical analysis and inferential statistical analysis in the form of classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination (R2). The results of descriptive statistical analysis illustrate that the Return On Asset variable is 6.86%, the Return On Equity variable is 34.86%, the Net Profit Margin variable is 26.62%, the Gross Profit Margin variable is 8.14% and Profit Growth 5.97% of all variables are included in the poor category. Based on the results of tests carried out partially, Return On Assets does not have a significant effect on profit growth. Meanwhile, Return on Equity, Net Profit Margin, and Gross Profit Margin have a significant effect on profit growth. So the simultaneous tests carried out show that Return On Assets, Return On Equity, Net Profit Margin and Gross Profit Margin simultaneously have a significant effect on profit growth. The resulting coefficient of determination (R2) shows that the contribution of the influence of the independent variable to the dependent variable is 58% and the remainder is influenced by other variables not examined in this research.